2019
DOI: 10.1093/esr/jcz034
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Differences in Welfare Chauvinism Between and Within Individuals Over Time: The Role of Subjective and Objective Economic Risk, Economic Egalitarianism, and Ethnic Threat

Abstract: A considerable portion of European citizens are in favour of limited or conditional access for migrants to welfare provisions. Previous studies found that this welfare chauvinism is stronger among citizens with less favourable economic positions. This study seeks to explain the relationship between economic risk, both objective and subjective, and welfare chauvinism by looking at two distinct mechanisms: the traditional economic explanation of economic egalitarianism and the cultural explanation of ethnic thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 42 publications
4
29
0
Order By: Relevance
“…Hence, in line with our argument, the less secure people feel the more exclusionary they become towards immigrants. Our findings are comparable to previous examinations where subjective economic risk is disclosed to have a direct and positive effect on welfare chauvinism in the UK and Netherlands after economic egalitarianism and ethnic threat perceptions are accounted for (Kros and Coenders, 2019). We show that a more comprehensive measure of subjective insecurity is also explanatory for welfare chauvinism even when we control for a long list of individual and contextual factors across several European countries.…”
Section: Empirical Strategysupporting
confidence: 82%
See 1 more Smart Citation
“…Hence, in line with our argument, the less secure people feel the more exclusionary they become towards immigrants. Our findings are comparable to previous examinations where subjective economic risk is disclosed to have a direct and positive effect on welfare chauvinism in the UK and Netherlands after economic egalitarianism and ethnic threat perceptions are accounted for (Kros and Coenders, 2019). We show that a more comprehensive measure of subjective insecurity is also explanatory for welfare chauvinism even when we control for a long list of individual and contextual factors across several European countries.…”
Section: Empirical Strategysupporting
confidence: 82%
“…Yet, it is also affirmed that subjective perceptions such as personal assessment of income, or own perception of being at risk are linked to chauvinistic attitudes (Heitzmann et al, 2018;Reeskens and van Oorschot 2012). Moreover, the effect of subjective and objective individual economic risk on welfare chauvinism is carried by respondents' perception of ethnic threat (Kros and Coenders, 2019). With regards to sociotropic concerns, it has been demonstrated that economic and cultural fears from migration are prevalent for immigration preferences whereas ethnic prejudice has a modest effect (Solodoch, 2020).…”
Section: Labor Market Status Cultural Threat and Ideologymentioning
confidence: 99%
“…And, individuals are unlikely to support redistribution across identity lines due to negative evaluations of outgroups (Kinder 1986;Gilens 1999;Wright and Reeskens 2013). A rich literature on welfare chauvinism --the stance that redistributive transfers should be restricted to solely ingroup members, or "our people" (Andersen and Bjorklund 1990, 212) --underscores ethnocentrism's effects on public support for welfare programs (e.g., Ford 2016;Harrell, Soroka, and Iyengar 2016;Kros and Coenders 2019). In sum, dominant groups are unlikely to support redistributive transfers when the primary beneficiaries are outgroup minorities, and thus salient identity differences undermine public support for a host of social welfare programs.…”
Section: Distributive Fairnessmentioning
confidence: 99%
“…Racialized reactions to welfare programs underscore the salience of ethnocentrism in evaluations of redistributive policies (Harell, Soroka, and Iyengar 2016;Kros and Coenders 2019;Reeskens and van Oorschot 2012;Wright and Reeskens 2013). Rooted in theories of realistic group conflict, welfare chauvinism suggests that ethnicity and race are the dividing lines of intergroup competition for resources.…”
Section: Ethnocentrism Policy Evaluation and Welfare Chauvinismmentioning
confidence: 99%
“…Ehrenreich, 1989). Recent survey-based studies confirm that a sense of "nostalgic deprivation"a subjective manifestation of socioeconomic riskis a major motivator behind support for PRRPs as well as welfare chauvinist attitudes (Gest et al, 2018;Kros & Coenders, 2019;Steenvoorden & Harteveld, 2018).…”
Section: Introductionmentioning
confidence: 99%